PROBLEMS AND PROSPECTS OF STANDARDIZING TAX AND CUSTOMS TERMINOLOGY IN THE UZBEK LANGUAGE - O.S. Akhmedov (American Journals, 2025)
This article analyzes the issues of linguistic regulation and unification of economic terminology actively used in the Uzbek language, with particular emphasis on terms that constitute its structural and lexical layers. Furthermore, the process of standardizing terminology in this field is based on the principle of precise conceptual expression in each language and the selection of correct and optimal term variants. However, in actual usage, instances are observed in which a single term denotes multiple concepts or, conversely, a single concept is represented by different terms. Based on these criteria, the article provides practical examples illustrating such terminological phenomena as internationalisms, variation (including doublets and synonymy), homonymy, polysemy, as well as expressive coloring, figurative meanings, and phraseological nuances present in certain economic terms.
Keywords: Tax, types of taxes, levies, economical terminology, terminological system, unification, lexical and semantical features, word structure, word building, translation, standardization.